2003
DOI: 10.1063/1.1573211
|View full text |Cite
|
Sign up to set email alerts
|

Destabilizing effect of plane Couette flow

Abstract: In contrast to its well-known stabilization of the low-frequency plasma motions, a shear flow may equally effectively destabilize a class of plasma modes. The latter quality of the flow is illustrated by studying an incompressible ideal plasma with a simple velocity profile ͑Couette flow in a finite interval͒; it is found that interchange modes are driven more unstable through their interactions with the shear flow. In the presence of the flow shear, the growth rate of the perturbation increases due to the cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…However, Tatsuno et al (2003) studied how a shear flow can destabilize a homogeneous magnetic field in the presence of an unstable density gradient. They found that a linear (Couette) velocity profile can be destabilizing when the velocity shear was not too strong.…”
Section: Introduction To Shear Flow Instabilitiesmentioning
confidence: 99%
“…However, Tatsuno et al (2003) studied how a shear flow can destabilize a homogeneous magnetic field in the presence of an unstable density gradient. They found that a linear (Couette) velocity profile can be destabilizing when the velocity shear was not too strong.…”
Section: Introduction To Shear Flow Instabilitiesmentioning
confidence: 99%
“…The sufficiency of the condition (13) immediately follows from the conservation law (10). The necessity is drawn from Eq.…”
Section: Reduced Magnetohydrodynamics and Its Basic Properties 21 Fomentioning
confidence: 99%
“…5, we discuss the destabilizing effect of shear flow [13]. In contrast to its well-known stabilization of the low-frequency plasma motions, a shear flow may equally effectively destabilize a class of plasma modes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations